A Computer-oriented Approach to the Comprehensive Organization of Information in Hand-compiled Medical Records - Certttti, S.; Longbxni, E.; Pinciholi, F. (Methods of Information in Medicine, 1979)
The problem of the comprehensive organization of the medical record is discussed in this paper. The basis of the organizational scheme is the integration of both fixed-text and free-text components with constraints imposed upon the original formatting of the free text. To support the diagnostic procedure a component of the record is a »diagnosis sheet«, which embodies a differential diagnosis approach and is discussed in detail.Results of more than two years of practical experience in the general medicine department of a regional hospital in Italy are presented. A trend towards a standardization of the medical terminology used was noted. Physicians' acceptance of a more rational conception of the medical record was high and a considerable flexibility in the language employed was observed. Finally, it is important to note that this new approach to the organization of the medical record was conceived in such a way as to make it processable by a computer located within the department itself. The initial experiences with the computerization of the record are presented and discussed with a view to future implementations and implications for cooperative, multidisciplinary research in medicine and information science.
Keywords: Medical Record; Information Processing; Free Text Analysis; Differential Diagnosis; Medical Training